2021
DOI: 10.1093/jtm/taab116
|View full text |Cite
|
Sign up to set email alerts
|

Experiences with pre-travel diagnostic PCR testing for SARS-CoV-2: challenges and opportunities

Abstract: This study explores challenges and opportunities arising from pre-travel SARS-CoV-2 diagnostics for the conduct of travel medicine clinics. We found that such testing might offer huge opportunities to reach individuals who would otherwise not present to travel medicine clinics, such as individuals visiting friends and relatives in malaria-endemic countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…The yield of this approach may be relatively limited. One study of German travelers, conducted between October 2020 and January 2021, found positive pre-travel tests in only 0.58% of 521 international travelers [ 72 ]. A PCR test done 2–3 days before departure may still miss an infected traveler in the incubation period that will become infectious during travel or shortly after arrival at their destination.…”
Section: Covid-19 Mitigation and Control Measuresmentioning
confidence: 99%
“…The yield of this approach may be relatively limited. One study of German travelers, conducted between October 2020 and January 2021, found positive pre-travel tests in only 0.58% of 521 international travelers [ 72 ]. A PCR test done 2–3 days before departure may still miss an infected traveler in the incubation period that will become infectious during travel or shortly after arrival at their destination.…”
Section: Covid-19 Mitigation and Control Measuresmentioning
confidence: 99%